Validity and reliability of the English version of the Student Evidence-Based Practice Questionnaire among Arabic-speaking undergraduate students at health sciences colleges: A cross-sectional study. (November 2022) - Youssef, Naglaa; Alharbi, Hanan
Abstract: Background: Evidence-based practice is vital for the provision of high-quality and safe healthcare. However, a rigorous, standardised, and unified evidence-based practice measure that could be applied to Arabic-speaking undergraduate students did not exist prior to this study. Moreover, translating questionnaires requires considerable time and money. Objectives: Thus, this study aimed to investigate the psychometric properties of the Student Evidence-Based Practice Questionnaire (English version) among Arabic-speaking undergraduate students at health sciences colleges in Saudi Arabia. Design: A cross-sectional survey was adopted. Settings: The survey was conducted online over a six-month period. Participants: A convenience sample of 395 undergraduate nursing students was recruited from health sciences colleges at seven universities in Saudi Arabia. Methods: The students were requested to complete the survey, including the Student Evidence-Based Practice Questionnaire, as well as a background and academic data sheet. Construct validity, discriminant sensitivity, and internal reliability were evaluated. Results: An exploratory factor analysis was performed. The Kaiser-Meyer-Olkin test value was 0.901, which was higher than the acceptable value of 0.70, indicating the adequacy of the sample size. Bartlett's test of sphericity was significant (chi-square (df: 210) = 4768.818, p < .001), indicating significant correlations within the variables and matrix. Based on Kaiser's criterion with eigenvalues > 1, four factors were detected that explained 62.03 % of the variance. The exploratory factor analysis of the 21 items generated factor loadings from 0.64 to 0.87. The Student Evidence-Based Practice Questionnaire has discriminant validity. The Cronbach's alpha and split-half reliability were over 0.7, indicating that the questionnaire had good internal consistency (Cronbach's alpha = 0.922). No evidence for floor or ceiling effects was observed. Conclusions: The English version of the Student Evidence-Based Practice Questionnaire has a satisfactory validity and reliability level and can be used among Arabic-speaking undergraduate students without the need to translate it into Arabic.